Pengaruh Kepuasan Kerja, Komitmen Organisasi dan Keadilan Prosedural Terhadap Kinerja Pegawai Dinas Pertanahan Kabupaten Pidie Jaya - Mahdi, Mahdi; Ibrahim, Ibrahim (Singkite Journal, 2025)
The study aims to prove the influence of job satisfaction, organizational commitment, and procedural justice on employee performance. Study at the Land Office of Pidie Jaya Regency, with 50 employees as research objects. Using quantitative survey data and associative methods applied with path analysis techniques. The results obtained: 1) There is a causal relationship between exogenous variables, namely job satisfaction, organizational commitment and procedural justice with a moderate category. 2) It is proven that there is a direct and indirect influence of each exogenous variable, namely job satisfaction on employee performance of 57.76%, organizational commitment of 21.43%, and procedural justice of 23.22%. 3) Simultaneously, job satisfaction, organizational commitment and procedural justice together affect the performance of employees of the Land Office of Pidie Jaya Regency with a contribution of 61.4%.